Louis Pasteur: The French Chemist Whose Experiment on Germs Led to the Greatest Medical Breakthroug - Birch, Beverley (Exley Publishing Ltd, 1990)
A biography of the nineteenth-century French scientist who discovered the process for destroying harmful bacteria with heat and opened the door to the new science of microbiology.
Keywords: Biography & Autobiography; Juvenile Nonfiction; Science & Technology